Banking and Fintech in the Digital Financial Ecosystem for the Unbankable Population - Ashari; Dewantoko, Tri Andi (Journal of Banks and Financial Institutions, 2025)
Objective: This research aims to analyze the role of banking and fintech in building an inclusive digital financial ecosystem for the unbankable. The main focus of the research is to identify challenges, opportunities, and optimal strategies in increasing access to financial services for segments of society that have not been reached by conventional banking. Research Design & Methods: This study employs a systematic literature review to synthesize existing research in the financial sector, ensuring methodological rigor and transparency while identifying key issues, research gaps, and areas for further exploration. Findings: The findings reveal that digitalization has significantly changed banking operations, requiring banks to enhance their technological capabilities and regulatory compliance. Fintech plays a crucial role in driving financial sector transformation by expanding access to financial services, especially for the unbanked population. However, cybersecurity risks and data privacy concerns remain key challenges. The success of digital banking transformation depends on technological adaptation, regulatory frameworks, and consumer trust. Implications & Recommendations: To create an inclusive and sustainable digital financial ecosystem, synergy between banks, fintechs, regulators, and communities is needed. Strategies include improving financial literacy, strengthening digital infrastructure, and developing regulations that support innovation without ignoring consumer protection. Contribution & Value Added: This study contributes by highlighting the synergistic role of banking and fintech in accelerating financial inclusion for the unbankable. It also offers strategic insights for stakeholders in designing more inclusive and sustainable digital finance policies and innovations.